Vascular Cell Adhesion Molecule-l (VCAM-l) in Graves' Disease: Its Association to Thyroid Status and Thyroid Receptor Stimulating Antibodies - Wan Nazaimoon, W.M.; Ismail, I.S.; Tan, H.J.; Kamaruddin, N.A.; Khalid, A.K. (2004)
Soluble vascular cell adhesion molecule-1 (sVCAM-1) and intercellular adhesion molecule-1 (sICAM-1) have been shown to be elevated in patients with Gravesâ disease and may play significant roles in the pathogenesis of the disease. The objective of this study was to measure the levels of sVCAM-1, sICAM-1, IL-6 and thyroid receptor stimulating antibodies (TRAb) in a cohort of hyperthyroid patients and determine their associations to thyroid hormones status, before and after 3 months therapy with carbimazole. Materials and Methods: Patients were given fixed daily dose of 20 mg carbimazole for 3 months and blood samples were collected at baseline and end of the study. Thirty eight patients were recruited from the Endocrine Clinic, Hospital University Kebangsaan Malaysia, con-sisting of 26 females and 12 males, age ranging from 16 to 65 years. Blood samples collected be-fore and at end of study were analyzed for TSH, Free T3, Free T4, thyroid receptor stimulating anti-bodies (TRAb), sVCAM-1, sICAM-1 and IL-6. Results: TRAb level of ?10 U/L was taken to be negative, while TRAb level of >10 U/L was considered as positive. Twenty-six patients (68) were TRAb positive (TRAb+) and 12 patients (30) were TRAb negative (TRAb-). Median TRAb in TRAb+ patients was 23 U/L at baseline, declining to 16.7 U/L (p<0.001) in the third 3 month. Serum sVCAM-1 levels were signifi-cantly elevated in TRAb+ patients compared to TRAb- (860 versus 499 ng/mL, p<0.001). The level decreased significantly to 537 ng/mL with treat-ment but remained higher than in TRAb- patients (p=0.003). Irrespective of TRAb status, all but one patient had elevated serum sICAM-1 levels that remained unaffected by carbimazole therapy. In contrast, IL-6 levels of hyperthyroid patients were within the reference range of 1.4-14.1 pg/mL. Baseline and post-treatment sVCAM-1, and not TRAb levels, were significantly corre-lated to thyroid hormones. Conclusion: Compared to other inflammatory markers, sVCAM-1 showed significant correlation to thyroid stimulating antibodies and was most sensitive to changes in thyroid status. The significance of these findings in relation to Gravesâ disease warrants further investigation.